EXPLANATION OF SCIENTIFIC VIEWS OF EASTERN THINKERS ON THE PROBLEM OF ADOLESCENCE AND ADDICTIVE BEHAVIOR - Mamajonova Shokhista Kamoldinovna (Bright Mind Publishing, 2025)
This article repeatedly emphasizes the importance of the role of the family and parents in raising a child by an Eastern thinker. The ideas are expressed that only the family environment from which the child lives gives the subtle specific aspects of his upbringing and behavior, and that the higher the moral qualities of the parents, the less negative behavioral changes will occur in the child.
Keywords: Adolescence, addictive behavior, Eastern thinkers, moral education, parents, child.